Guide imagery and music (GIM) untuk menurunkan kecemasan kompetitif pada atlet sebelum bertanding - Al Amin, Muhamad Febrian; Iswinarti, Iswinarti (University of Muhammadiyah Malang, 2020)
Objectives: Anxiety in sports is one of the factors that affect athlete performance when facing a match. Anxiety that arises not only consists of cognitive components, but also involves physiological or somatic components. This study aims to examine the effect of guide imagery and music (GIM) interventions in overcoming competitive anxiety in athletes before competing.Method: The subjects consisted of three experimental groups and one control group of futsal athletes. The questionnaire used was a competitive Anxiety scale that was compiled by the researcher himself for data collection. The research design used was quasi-experimental with non-randomized pretest-posttest control group design. Data analysis used non-parametric analysis, namely the Wilcoxon, Kruskal-Wallis and Mann Whitney Tests.Findings: The results showed the Guide Imagery and music intervention was effective in reducing athletes' competitive anxiety. This result can be seen from the decrease in competitive anxiety scores in the experimental group during the pre-test and post-test. In addition, there was a significant difference in competitive anxiety when a different test was performed with the Mann Whitnney Test between the experimental group and the control group.Conclusions: Guide Imagery and music therapy can be used to reduce competitive anxiety in athletes before a match.